Gravitational model: analysis of mutual trade of the Eurasian Economic Union countries - O. N. Zhilkin; S. A. Balashova; A. A. Abramova (Вестник университета, 2023)
This study presents the aggregative data analysis concerning foreign trade of the Eurasian Economic Union (hereinafter referred to as EAEU) countries. A gravity model of the foreign trade in several modifications between 2011 and 2019 (the period before the COVID-19 pandemic) was applied. On the basis of the conducted research it was discovered how fast the impact of the distance factor between foreign economic partners decreases with consideration to the time factor. Also those industries and spheres of activity were identified where the factor may be the least important or where the model is not applicable at all. Besides, the authors gave recommendations to include additional factors in the gravitational model if it is applied for analysis and forecasting of foreign trade with border states or states that are not part of the EAEU.